ANALISIS PENGARUH RUTE BUSWAY TERHADAP RUTE ANGKUTAN UMUM LAINNYA (Studi Kasus : Koridor 11 Pulogebang â Kampung Melayu) - , HENDRIK PRASETIYO; , Prof. Ir. Sigit Priyanto, M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
. Operation Route 11 busway corridors impact on the operational performance of the old public transport services, particularly the route intersects with the busway route, which resulted in decreasing the performance of public transport services., For it is necessary to analysis the influence of Busway routes to other public transportation routes, so that the service public transport is not a bad or even be nice The method of analysis used in this thesis research is the analysis of the performance of public transport services and financial analysis (BOK and feasibility), the above analysis is used to see the performance of the public transport services that operate today in Jakarta to be compared with the standard of service been recommended by the World Bank. Analysis of the performance of public transport services, the indicators - indicators include: waiting time, travel time, modal transfer rate, and a walking distance. The analysis shows that since the operation of the busway corridor 11, public transport and unloading long period of decline and revenue factors, it is necessary to do a strategy that operators do not suffer losses continuously, by rationalizing transport or shift hours of operation with the introduction of public transport, so that income increased so that the operator of public transport services has improved.